DOES GENDER REALLY AFFECT SHOPPING PATTERNS? - ABRUDAN, Ioana-Nicoleta (Studia Universitatis Babeș-Bolyai Negotia, 2016)
Movies, jokes, books and folklore are full of stereotypes on the differences between men and women. Of these, one of the most known and accepted, even in academic literature, is related to differences in shopping behavior of men and women. Women are “renowned” for indulging themselves in shopping as a form of therapy, of relaxation and pastime. Departing from this largely accepted dogma, that women love shopping, and that they spend more time and money on both products and services, a generalization on differences on all aspects of shopping may be inferred. But are they really that different from men with respect to shopping habits? The aim of the present study is to question whether these assumptions about the differences between women and men shopping behavior are indeed true. The results indicate differences in shopping orientations, but no statistically significant differences regarding the amount of money and time spent shopping and similarities on all the other facets of shopping included in the study - formats preferred, days of the week spent shopping, distance traveled to the stores, accompanying parties when shopping, impulse shopping behavior.